Evaluating the UV-C sensitivity of Coxiella burnetii in skim milk using a bench-scale collimated beam system and comparative thermal sensitivity study by high-temperature short-time pasteurization - Pendyala, Brahmaiah; Vashisht, Pranav; Chen, Fur-Chi; Sanchez, Savannah E.; Comstock, Bob; Omsland, Anders; Patras, Ankit (Frontiers in Food Science and Technology, 2023)
Coxiella burnetii is a zoonotic Gram-negative obligate intracellular bacterial pathogen and the causative agent of Query (Q) fever in humans. Contamination of milk by C. burnetii as a consequence of livestock infection is a significant public health concern. Effective methods to inactivate C. burnetii in milk is a critical aspect of food safety. We hypothesize that the implementation of non-thermal UV-C processing technologies in the dairy industry can effectively preserve the sensory, nutritional, and structural qualities of raw milk products while ensuring their safety, making them a viable alternative to traditional high-temperature short-time (HTST) pasteurization methods. In this study, we measured optical light attenuation factors; absorption, scattering, and reflection of skim milk (SM) and considered for evaluation of delivered UV dose under stirred conditions. The verification studies were conducted using Escherichia coli ATCC 25922 inoculated in phosphate buffer (transparent fluid), and humic acid (opaque fluid). Absorption, scattering coefficient, and the reflectance of SM at 254 nm were measured as 19 ± 0.3/cm. 26 ± 0.5/cm and 10.6 %, respectively. SM inoculated with an avirulent strain of C. burnetii was irradiated using a collimated beam device equipped with a low-pressure UV-C 254 nm lamp at doses from 0 – 12 mJ/cm2. Results showed a log-linear inactivation of C. burnetii in SM with UV-C sensitivity (D10) value of 4.1 ± 0.04 mJ/cm2. Results of HTST pasteurization (72 ºC/15 sec) revealed that C. burnetti was observed to be heat sensitive with a D value of 1.8 secs. Salmonella enterica serovar Muenchen ATCC BAA 1674 in SM showed similar UV inactivation kinetics and thereby is suggested as a suitable surrogate to C. burnetii for pilot scale UV-C processing studies of SM.